Personal Carbon Trading, Carbon-Knowledge Management and Their Influence On Environmental Sustainability In Thailand - Dally, Dadang; Kurhayadi, Kurhayadi; Rohayati, Yeti; Kazemian, Soheil (International Journal of Energy Economics and Policy, 2020)
The relationship between personal carbon trading, carbon knowledge management and their impact on the environmental sustainability has got very little attention. Inspired from this gap in the literature, present research is exploring the relationship between carbon trading, carbon knowledge and their combine impact on sustainability of the natural environment in Thailand. A questionnaire is designed based on the various factors of both exogeneous and endogenous variables of the study. A sample of 251 respondents was collected for both measurement and structural equation models. Additionally, some descriptive measures are also calculated and presented which provide the fact that all items have been observed with moderate responses from the targeted respondents. It is found that there is a significant and positive influence of personal carbon trading on environmental sustainability. For the knowledge management, three dimensions like knowledge acquisition, knowledge dissemination, and knowledge responsiveness were also added in the structural model. Findings further explain that out of these three factors, there is a significant and positive influence of carbon knowledge acquisition and carbon knowledge responsiveness on environmental sustainability in Thailand. However, influence from carbon knowledge dissemination is insignificant on environmental sustainability. As per the practical implication, this study is found to be an initial effort to explore the relationship between the targeted variables, specifically in Thai economy. However, some limited context for this research is also observed like expanding the sample size and implication in other nearby regions too. Keywords: personal carbon trading, carbon knowledge management, environmental sustainability JEL Classification: Q19 DOI: https://doi.org/10.32479/ijeep.10617